1) f(0)= -6
, f(2)= -12, f(-1)= 0, f(6)= 0
2) f(0)= -12
, f(2)= -8
, f(-1)= -14
, f(6)= 168
3) f(0)= 5
, f(2)= 20, f(-1)= 2.5
, f(6)= 320
Step-by-step explanation:
1) The given function is f(x) = x² – 5x – 6.
To find the values of f(0)
, f(2), f(-1), f(6) :
Substitute x=0 in f(x) = x² – 5x – 6
f(0) = -6
Therefore, f(0) = -6
Substitute x=2 in f(x) = x² – 5x – 6
f(2) = (2)² -5(2)-6
⇒ 4-10-6
⇒ 4-16
⇒ -12
Therefore, f(2) = -12
Substitute x= -1 in f(x) = x² – 5x – 6
f(-1) = (-1)² - 5(-1) -6
⇒ 1+5-6
⇒ 6-6
⇒ 0
Therefore, f(-1) = 0
Substitute x= 6 in f(x) = x² – 5x – 6
f(6) = (6)² - 5(6) -6
⇒ 36 -30 -6
⇒ 36-36
⇒ 0
Therefore, f(6) = 0
2) The given function is f(x) = x³– x²–12.
To find the values of f(0)
, f(2), f(-1), f(6) :
Substitute x=0 in f(x) = x³– x²–12
f(0) = -`12
Therefore, f(0) = -12
Substitute x= 2 in f(x) = x³– x²–12
f(2) = (2)³ - (2)² -12
⇒ 8-4-12
⇒ 8-16
⇒ -8
Therefore, f(2) = -8
Substitute x= -1 in f(x) = x³– x²–12
f(-1) = (-1)³ - (-1)² -12
⇒ -1-1-12
⇒ -14
Therefore, f(-1) = -14
Substitute x= 6 in f(x) = x³– x²–12
f(6) = (6)³ - (6)² -12
⇒ 216 -36 -12
⇒ 216-48
⇒ 168
Therefore, f(6) = 168
3) The given function is f(x) = [tex]5.24^{x}[/tex]
To find the values of f(0)
, f(2), f(-1), f(6) :
Substitute x=0 in f(x) = [tex]5.2^{x}[/tex]
f(0) = 5 × [tex]2^{0}[/tex]
Any number with power zero is 1.
f(0) = 5
Therefore, f(0) = 5
Substitute x=2 in f(x) = [tex]5.2^{x}[/tex]
f(2) = 5 × 2²
⇒ 5×4
⇒ 20
Therefore, f(2) = 20
Substitute x= -1 in f(x) = [tex]5.2{x}[/tex]
f(-1) = [tex]5\times2^{-1}[/tex]
⇒ 5 × 1/2
⇒ 5 × 0.5
⇒ 2.5
Therefore, f(-1) = 2.5
Substitute x= 6 in f(x) = [tex]5.2^{x}[/tex]
f(6) = [tex]5\times 2^{6}[/tex]
⇒ 5 × 64
⇒ 320
Therefore, f(6) = 320